The Socio-cultural Portrait and Jampak Local Wisdom of Mpur Tribe’s People in Tambrauw Regency: West Papua Province - Asimi, Tonci (International Journal of Psychosocial Rehabilitation, 2020)
The subject matter of the research is to describe Jampak local wisdom in the socio-cultural portrait of Mpur Tribe’s people in Tambrauw Regency, West Papua Province. The purpose of the research is to describe how Jampak local wisdom is in the socio-cultural portrait of Mpur Tribe’s people. The research used a qualitativedescriptive method by a library research approach that is, using books and other literature as the main object and source. Jampak is one of the traditional houses of those Mpur Tribe’s people who inhabit Tambrauw Regency, West Papua Province. It can be used as the place at which adat (traditional) parties of Mpur Tribe’s people in Tambrauw Regency, West Papua Province, are performed. The research findings revealed that Jampak local wisdom in the sociocultural portrait of Mpur Tribe’s people in Tambrauw Regency, West Papua, was not optimal yet, due to three factors, namely globalization, education, and outsider migration.